2011
DOI: 10.1097/fbp.0b013e3283423d6b
|View full text |Cite
|
Sign up to set email alerts
|

Tail suspension test does not detect antidepressant-like properties of atypical antipsychotics

Abstract: The purpose of this study was to investigate the potency of atypical antipsychotics (clozapine, olanzapine, amisulpride, quetiapine, aripiprazole, risperidone) to reduce immobility time and to increase the fighting power, and the number of fights in an automated version of the tail suspension test in C57BL/6J mice. Antidepressant drugs, citalopram and imipramine were tested for comparison. Olanzapine (0.125-5 mg/kg), amisulpride (0.5-2 mg/kg), quetiapine (0.25-2 mg/kg), aripiprazole (0.25-1 mg/kg), and risperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Moreover, its potential adverse effects, i.e., the risk of causing catalepsy and sedation, were tested in the bar test and the spontaneous locomotor activity test, respectively (Table ). , …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, its potential adverse effects, i.e., the risk of causing catalepsy and sedation, were tested in the bar test and the spontaneous locomotor activity test, respectively (Table ). , …”
Section: Resultsmentioning
confidence: 99%
“…This antipsychotic is among the most effective in reducing suicidality, a parameter which is strongly connected to depressed mood (Meltzer 2012). Previous studies of clozapine in the FST have shown that it is also active under other experimental conditions (Chindo et al 2012) and, in a comparative study in mice, was the only antipsychotic that showed activity in the tail-suspension test (Wesolowska et al 2011). It therefore seems that clozapine’s mood-modulating effects are clearly measurable in pharmacological models, and this might provide a criterion by which to evaluate novel drugs at an early stage of drug discovery.…”
Section: Discussionmentioning
confidence: 98%
“…One of the most established behavioral rodent model of mania is based on the measurement of psychostimulantinduced hyperactivity, a behavior that is reproducibly attenuated by a number of treatments used in mania, including lithium, valproate, and antipsychotics [45,46]. Studies performed in this model have suggested that PKC could be involved in the modulation of manic-like behavior.…”
Section: Behavioral Effects Of Pkc Modulators On Animal Models Of Manmentioning
confidence: 99%